Antibacterial ativity of biosynthesized silver nanoparticles against Pseudomonas aeruginosa in vitro: Ahmad N. A. Salih1 Orooba M.S. Ibrahim1 Mohammad J. Eesa2 - Salih, Ahmad N. A.; Eesa, Mohammad J. (The Iraqi Journal of Veterinary Medicine, 2017)
This study was conducted for the synthesis of silver nanoparticles by using olive leaves aqueous extract and evaluate its antibacterial activity against Pseudomonas aeruginosa in vitro. The synthesis and characterization of silver nanoparticles was confirmed by Ultra Violet Visible – spectrophotometer and Scanning Electron Microscopy. Well diffusion method was used to show the antibacterial action of silver nanoparticles against Pseudomonas aeruginosa in vitro in comparison with standard antibacterial silver sulfadiazine by using different concentrations of each agent ranged from 12.5-200 μg/ml. The results of this study showed it possible to produce silver nanoparticles in eco-friendly and easy process and UV-Visible absorption spectra of the silver nanoparticles revealed maximum absorbance at 420 and 430 nm. The Scanning Electron Microscopy analysis demonstrated the mean of the silver particles diameter was 26 nm. The antibacterial findings of the synthesized silver nanoparticles against Pseudomonas aeruginosa in vitro showed that the silver nanoparticles were more effective than silver sulfadiazine against Pseudomonas aeruginosa. It could be concluded that olive leaves extract can be used effectively in the production of silver nanoparticles and these synthesized nanoparticles had considerable antibacterial activity against Pseudomonas aeruginosa in vitro.